Investigating music therapists' approaches to the assessment of musical material. Issue 1 (1st June 2016) - Letulė, Nerdinga; Thompson, Marc; Erkkilä, Jaakko
Abstract : Background : There is a body of literature that recognises the importance of accurate assessment in music therapy, but no consensus regarding the meaning and importance of the musical processes is taking place. Objective : This presentation aims to bridge the gap between scientific research and common clinical practice by exploring how music therapists address the assessment of musical material in their clinical work. Methods : Eight professionally renowned music therapists have been recruited using referral sampling, all with a high level of professional experience in psychodynamic music therapy. In-depth, semi-structured interviews captured therapists' personal experiences and opinions on the role of music in assessment and the applicability of different assessment methods for different client groups. Constructivist grounded theory was employed in order to analyse the interviews. Discussion : The links between clients' musical expression and psychological issues will be discussed. Conclusions : The factors influencing therapists' approaches to the assessment of musical material will be presented.